Restorative justice in Spain after the Law on the Efficiency of the Public Justice Service: Opportunities and Challenges (Justicia &Derecho, 2025)
The Spanish criminal procedural system is retributive. However, in recent decades mediation has been introduced as a complement to the criminal process, attributing certain benefits to the accused when the parties (victim and defendant) reach a restorative agreement. These experiences began without a law to support them, although gradually legislation was enacted through measures that focused mainly on the victim’s right to reparation. The recent Law on the Efficiency of the Public Justice Service, of January 2025, takes a further step forward. It introduces a provision in the Criminal Procedure Law relating to Restorative Justice. This paper analyzes this regulation, highlighting strengths as well as aspects that we consider unclear or problematic.
Keywords: restorative justice; criminal mediation; criminal proceeding; ADR